Legalism, Antinomianism, Situationism: Three Moral Decision-Making Orientations - Gillmore, Gerald M. (Review of religious research, 1974)
Three contemporary adult, moral decision-making orientations were operationalized. Legalism appeals first to laws and principles given by a supra-personal authority. Antinomianism attempts to make moral decisions consistent with internal values and personal growth. Situationism, while treating the rules and values of society seriously, violates these rules if human welfare is best served by so doing. One hundred ten volunteer Introductory Psychology students evaluated choices described in a series of stories and responded to three scales of Likert-type attitude-belief items and a religiosity scale. Results were consistent with the initial theory of Legalism. This was largely true of Antinomianism as well, but not true for Situationism which was ultimately rejected in favor of what is essentially the subordination of external authority and the self to the primary moral value of others.